Factor Structure of Organizational Commitment: Differences between U.S. and South Korean Samples - Lee, Jo Ann; Yang, Chulguen (Psychological Reports, 2005)
The current study compared the factor structures of the construct of organizational commitment between two samples of financial employees, one from the U.S. ( n = 103) and one from South Korea ( n = 109). Participants completed a 26-item questionnaire. Two factors (an affective component and a normative component) emerged for the U.S. sample; only one factor for the Koreans. Results suggest that culture should be considered when trying to assess organizational commitment.
Keywords: dept.mgt; peer-reviewed

A Clash of Capitalisms: Foreign Shareholders and Corporate Restructuring in 1990s Japan - Ahmadjian, Christina L.; Robbins, Gregory E. (American Sociological Review, 2005)
This article examines the clash between stakeholder- and shareholder-based business systems resulting from an increase in foreign portfolio investment in the Japanese economy during the 1990s. An analysis of 1,108 firms between 1991 and 2000 shows that as foreign institutional investors, who were more interested in investment returns than in long-term relationships, replaced domestic shareholders, one fundamental pillar of Japan's stakeholder capitalism began to crack. Japanese firms began to adopt downsizing and asset divestiture, practices more characteristic of Anglo-American shareholder economies. The influence of foreigners, however, was weaker in firms more deeply embedded in the local system through close ties to domestic financial institutions and corporate groups. Thus, foreign investors were influential primarily in firms less embedded in the existing stakeholder system. This research contributes to debates on globalization and convergence of business systems, institutional change, and corporate governance systems.
Keywords: dept.mgt; peer-reviewed

The Evolution and Commercialization of Wind Power Technology. - Laird, Kenneth R. (2005)
Keywords: dept.mgt; faculty_collection; sabbatical_report

Past journeys: Global lessons learned from entrepreneurial women in US history - Oppedisano, J. (International Handbook of Women and Small Business Entrepreneurship, 2005)
Keywords: dept.mgt